A visit to madinah - Khan, Saniyasnain (GoodwordKidz New Delhi, 2004)
This story describes a heartfelt journey to Madinah, highlighting its historical and spiritual significance. It emphasizes the deep connection and love for the Prophet$1 (Bs city among believers.s